Wartość "Septuaginty" w rozumieniu św. Hilarego z Poitiers - Stanula, Emil (Vox Patrum, 1984)
Analyzing some of St. Hilary’s of Poitiers statements, included in the "Tractatus super Psalmos", we come to the conclusion that the objective value of Septuaginta depends on three things.